(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Objective 1: To determine the rate of positive patient experience among inpatients at Tien Giang Provincial General Hospital in 2024. Objective 2: To improve the rate of positive patient experience for inpatients at Tien Giang Provincial General Hospital during the period 2024-2026. Materials and methods: A cross-sectional descriptive study; surveying patients who visited and received inpatient treatment at Tien Giang Provincial General Hospital from January to December 2024. Results: The overall rate of positive inpatient experiences ranged from 81.78% to 98.96%. The highest experience was reported prior to discharge (98.96%), followed by billing experience (95.32%) and admission experience (89.59%). The lowest rate of positive experience was reported during the hospitalization period, with 81.78%. Conclusion: Appropriate strategies are needed to improve the rate of positive patient experiences for inpatients at Tien Giang Provincial General Hospital during the period from 2024 to 2026.